HARMONISASI TRADISI MEPERAS SENTANA DALAM PERSIDANGAN PERMOHONAN PENGANGKATAN ANAK DI PENGADILAN NEGERI DENPASAR - ARTHANI, NI LUH GEDE YOGI; Kumala Dewi, Ni Komang Ratih; Lestari, Anak Agung Adi; Dita Sari, Ni Nyoman Candra; Adnyadewi, Ni Made Santi (Jurnal Aktual Justice, 2024)
Adoption is a solution for couples unable to have children. In Bali, adoption involves a traditional ceremony known as meperas sentana, which holds spiritual and social significance under Balinese customary law. This study aims to analyze the reasons behind the performance of the meperas sentana ceremony prior to the child adoption process in the Denpasar District Court, examining both customary and formal legal aspects. The findings reveal that 52% of respondents understand adoption according to Balinese customary law, while 68% are familiar with adoption under national law. The varying levels of understanding highlight the need for increased socialization of both legal systems. This study provides insights into the importance of balancing the preservation of local traditions with compliance with national law in child adoption practices in Bali.